Implementation Of Learning Program Life Skill at SD Negeri Tonala, Posigadan District, South Bolaang Mongondow Regency - Sri Novita Tuli; Zulaecha Ngiu; Sukarman Kamuli (Cita konsultindo, 2025)
The purpose of this study to (1) Transformation in learning Life Skill at SD Negeri Tonala, Posigadan District, South Bolaang Mongondow Regency. (2) Implementation of Learning Life Skill at SD Negeri Tonala, Posigadan District, South Bolaang Mongondow Regency. This research was conducted at SD Negeri Tonala, Posigadan District, South Bolaang Mongondow Regency, which has been established since 1979 and is accredited A. This research uses a qualitative descriptive approach with interview, observation, and documentation techniques. Data were collected from the principal, teachers, students, and parents to determine the implementation of life skill learning in schools.The research results show (1) Transformation in learning Life Skill at SD Negeri Tonala, Posigadan District, South Bolaang Mongondow Regency, including through (a) Self-awareness (b) personality formation (c) independence. (2) Implementation of Learning Life Skill at SD Negeri Tonala, Posigadan District, South Bolaang Mongondow Regency, among others, through (a) personal skills (b) social skills (c) intellectual skills. Suggestions are expected to further improve the implementation of learning programs. Life Skill which is accompanied by the principal’s efforts to improve Teacher competency in accordance with the demands of scientific and technological developments. Most importantly, teachers develop new methods and strategies in learning